Cholesterol depletion of hepatoma cells impairs hepatitis B virus envelopment by altering the topology of the large envelope protein - Dorobantu, C; Macovei, A; Lazar, C; Dwek, R; Zitzmann, N; Branza-Nichita, N (American Society for Microbiology, 2011)
Previous reports have shown that cholesterol depletion of the membrane envelope of the hepatitis B virus (HBV) impairs viral infection of target cells. A potential function of this lipid in later steps of the viral life cycle remained controversial, with secretion of virions and subviral particles (SVP) being either inhibited or not affected, depending on the experimental approach employed to decrease the intracellular cholesterol level. This work addressed the role of host cell cholesterol on HBV replication, assembly, and secretion, using an alternative method to inhibition of the enzymes involved in the biosynthesis pathway. Growing HBV-producing cells with lipoprotein-depleted serum (LPDS) resulted in an important reduction of the amount of cholesterol within 24 h of treatment (about 40%). Cell exposure to chlorpromazine, an inhibitor of the clathrin-mediated pathway used by the low-density lipoprotein receptor for endocytosis, also impacted the cholesterol level; however, this level of inhibition was not achievable when the synthesis inhibitor lovastatin was used. HBV secretion was significantly inhibited in cholesterol-depleted cells (by ∼80%), while SVP release remained unaffected. The viral DNA genome accumulated in LPDS-treated cells in a time-dependent manner. Specific immunoprecipitation of nucleocapsids and mature virions revealed an increased amount of naked nucleocapsids, while synthesis of the envelope proteins occurred as normally. Following analysis of the large envelope protein conformation in purified microsomes, we concluded that cholesterol is important in maintaining the dual topology of this polypeptide, which is critical for viral envelopment.